Developing a Flip PDF-Based Interactive Module to Enhance Self-Care Skills for Students with Intellectual Disabilities - Yusrawati, Yusrawati; Nurhastuti, Nurhastuti; Asnah, Megaiswari Biran; Tsaputra, Antoni; Rahmahtrisilvia, Rahmahtrisilvia (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop an interactive teaching module using the Flip PDF Corporate Edition application and evaluate its validity, practicality, and effectiveness in enhancing self-care abilities among students with intellectual disabilities. The research employed a Research and Development (R&D) method, following the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The trial subjects comprised teachers and students from SLBN 1 Pariaman and SLBN 2 Pariaman, West Sumatera. Data collection involved validation questionnaires, practicality observation sheets, and pretest-posttest assessments. Descriptive statistics were used to analyze validation and practicality test results, while the Wilcoxon signed-rank test evaluated the difference between pretest and posttest scores. The results indicated that the module was highly valid, with an average score above 80%, and practical, with positive responses from teachers and students. The Wilcoxon test revealed a significant improvement between pretest and posttest scores (p = 0.018), demonstrating the module’s effectiveness in enhancing self-care abilities. Therefore, the module is suitable for use as a learning medium in special self-care education programs.